2021
DOI: 10.1126/sciadv.abc7170
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin-1–enriched microenvironment drives endothelial injury and vascular rarefaction in chronic kidney disease

Abstract: Endothelial cell injury leading to microvascular rarefaction is a characteristic feature of chronic kidney disease (CKD). However, the mechanism underlying endothelial cell dropout is poorly defined. Here, we show a central role of the extracellular microenvironment in controlling endothelial cell survival and proliferation in CKD. When cultured on a decellularized kidney tissue scaffold (KTS) from fibrotic kidney, endothelial cells increased the expression of proapoptotic proteins. Proteomics profiling identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 44 publications
(60 reference statements)
0
45
0
Order By: Relevance
“…Thus, our result indicates that CCBE1 might be also participating in the IPF progression and suggests that it could be contributing in the fibrogenesis associated with cancer, such as the fibrosis that precede the liver cancer appearance, an intriguingly phenomenon that should be addressed. Interestingly, some up-regulated proteins that we identified had already been reported as key players in the pathogenesis of fibrotic diseases, such as TNC, IGFBP7, FBN1, COL5A2, COL5A1, COL3A1, COL1A2, COL1A1 and COL6A1) [40][41][42][43]. Interestingly, these proteins were identified as part of a relevant module in the PPI network of differentially expressed proteins, indicating that these proteins are biologically interconnected.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, our result indicates that CCBE1 might be also participating in the IPF progression and suggests that it could be contributing in the fibrogenesis associated with cancer, such as the fibrosis that precede the liver cancer appearance, an intriguingly phenomenon that should be addressed. Interestingly, some up-regulated proteins that we identified had already been reported as key players in the pathogenesis of fibrotic diseases, such as TNC, IGFBP7, FBN1, COL5A2, COL5A1, COL3A1, COL1A2, COL1A1 and COL6A1) [40][41][42][43]. Interestingly, these proteins were identified as part of a relevant module in the PPI network of differentially expressed proteins, indicating that these proteins are biologically interconnected.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, it has been demonstrated that FBN1 is overexpressed in renal tissue and that its deletion decreases the injury and fibrosis induced by unilateral ischemia-reperfusion injury (UIRI) in a murine model of renal fibrosis. In addition, FBN1 has been described to inhibit proliferation and promote endothelial cell apoptosis [42]. However, to our knowledge, it had not been reported yet whether FBN1 contained in EVs plays a role in the development of other fibrotic diseases such as IPF.…”
Section: Discussionmentioning
confidence: 90%
“…These changes became evident mainly from 12 h onwards and were characterized by inhibited or decreased release of a variety of compounds, such as Htra1 and Prss23, serine proteases highly expressed in the ovary and modulated by estrogens, and LH [ 13 , 48 ], and factors that usually sustain cell survival, such as the antioxidant and antiapoptotic Prdx2 and Hbat1, the metabolic regulators Ldha and Pkm, and the regulator of apoptotic pathways Tmsb4x [ 20 , 21 , 22 , 23 , 46 , 47 ]. At the same time, CIS appeared to increase the release of several proteins that generally favor apoptosis, such as Amh and the ECM protein Fbn1 reported to be able to induce this process in the follicular cells [ 43 , 49 , 50 ], the cytokine Fam3c [ 44 ], Ecm1 [ 36 ], the 14-3-3 family hub protein Ywhaz [ 39 ], and the protease Ctsb [ 51 ]. The drug, however, seemed also able to induce the release of proteins usually exerting antiapoptotic effects, such as Adam12 [ 52 ], Agt [ 53 , 54 , 55 ], Tpt1 [ 37 ], Cstb [ 28 ], and Tuba1c [ 29 ], probably representing the attempt of the tissue to counteract the death processes, and of Ahnak, an unusual desmoyokin scaffolding protein with a role in diverse processes, such as cell structure and migration, calcium channel regulation, and tumor metastasis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…7). It was reported that TNF-α can upregulate VCAM-1 through the NF-κB pathway [30,[41][42][43], but CLT could act as an inhibitor of NF-κB [9,12,15,16,[36][37][38][39]. Hence, it is possible that CLT inhibit the expression of downstream VCAM-1 via downregulating both TNF-α and NF-κB pathway.…”
Section: Mechanic Study Of Clt On Nephritis Treatmentmentioning
confidence: 99%
“…CLT has anti-inflammatory, anti-oxidant, immunosuppressive and antitumor effects [3][4][5][6][7][8][9][10]. As an ingredient of TCM, it displays significant therapeutic effects on various inflammatory diseases and autoimmune diseases [4,5,7,[10][11][12][13][14][15][16]. In China, CLT has been widely used in the treatment of various kidney diseases.…”
Section: Introductionmentioning
confidence: 99%